Cytogenetic analysis in western Atlantic snappers (Perciformes, Lutjanidae) - Rocha,Érika Cruz (2008)
The Lutjanidae or snappers are a family of perciform fishes, mainly marine but with some members living in estuaries and entering fresh water to feed. Some are important food fish. Cytogenetic data for Lutjanidae are scarce. In the present work, we cytogenetically characterized through conventional Giemsa staining techniques, Ag-NOR and C-banding the species Ocyurus chrysurus, Lutjanus analis, L. alexandrei, L. cyanopterus, L. jocu and L. synagris, all found along the Brazilian coast. Karyotype analysis of all six species showed a modal value of 2n = 48 acrocentric chromosomes. Single NORs were found at pericentromeric position on the long arms of the 2nd pair in O. chrysurus, L. alexandrei and L. cyanopterus, on the 5th pair in L. analis and on the 23rd pair in L. synagris. The species L. jocu presented multiple NORs located on the 2nd pair at a pericentromeric region and on the 5th pair at a telomeric region. Heterochromatic blocks were identified at the centromeric region of all chromosomes of the studied species. These results indicate that, despite of the chromosomal stability of this family, a relative structural diversification seems to have occurred in the chromosome evolution of the group. Such diversification was evidenced by divergent number and location of ribosomal sites among species. The NOR-bearing pairs represented an efficient cytotaxonomic marker for most of the analyzed species. The data suggest that the presence of interstitially located single NORs on a large acrocentric pair should represent a basal condition for lutjanids.